Argentina : Reforming Policies and Institutions for Efficiency and Equity of Public Expenditures - World Bank (Washington, DC, 2013)
This report seeks to identify policy, and institutional reforms to enhance the efficiency, equity, and effectiveness of public expenditures at the federal, and provincial levels in Argentina. These are crucial to generate the kinds of fiscal surpluses needed for fiscal solvency, and macroeconomic stability. Otherwise, efforts to stimulate private-sector-led growth, and generate employment - which are key for sustained poverty reduction - may not succeed. The report analyzes both sectoral, and process-related issues. The sectoral analysis focuses on the major expenditure categories within the social, and infrastructure sectors, which accounts for over 70 percent of total expenditures. Effective provision of social, and infrastructure services is crucial for poverty reduction, equity, and improved living standards. The process-related issues focus on two areas affecting expenditure efficiency, and fiscal solvency: federal-provincial government relations, and public expenditure management. Though important, federal tax policy, and public administration issues are excluded from this report in order to keep its scope manageable. The report further highlights that only the private sector is able to finance Argentina's projected infrastructure investments. To this end, investor confidence will need to be restored, which will in turn, require concluding the renegotiations with private operators, and addressing certain second-generation reforms. The alternative of a return to public ownership, and control is not desirable, given the higher efficiency in the private sector, the other demands on fiscal resources, and problems with public provision of services. As outlined below, what Argentina needs is a fair resolution of renegotiations, better regulatory arrangements, better protection for the poor, and better financing mechanisms.